Perpetual creativity in the perfection of God: Ibn Taymiyya's Hadith commentary on God's creation of this world - Hoover, Jon (Oxford University Press, 2004)
The course of the Islamic debate over the origin of the world through Ibn Rushd (d. 595/1198) is well known. Kalam theologians and al-Ghazali seek to prove the temporal origination of the world, while philosophers such as Ibn Sina argue for the world's eternal emanation from God. Ibn Rushd reasserts the world's eternity against al-Ghazali, portraying creation, however, not as emanation but as a perpetual process rooted in God's perfection. Almost completely unknown to Western-language scholarship is that the Hanbali theologian Ibn Taymiyya (d. 728/1328)—known in some quarters to be anti-rationalist—makes a philosophical contribution to this debate and follows very closely in the footsteps of Ibn Rushd. As a first step in the more extensive study that Ibn Taymiyya's views on creation deserve, this article introduces and translates his commentary on the hadith found in Bukhari, ‘God was, and there was nothing before Him, and His Throne was on the water … Then, He created the heavens and the earth’. In this commentary, Ibn Taymiyya sets forth a speculative theological model of God's perpetual creativity. Although neither the world nor any one part of it is eternal, God's perfection entails that He create one thing or another from eternity. Ibn Taymiyya maintains that this philosophically derived vision of God accords with revelation, and it forms the viewpoint from which he polemicizes against Kalam theologians and Ibn Sina on creation.